The ecology of sunda pangolin in Kabili-Sepilok Forest Reserve, Sabah - Elisa Panjang (2015)
Sunda pangolin (Manis javanica) is an ant/termite eater, listed as a critically endangered species under the IUCN and is categorized in Appendix II under OTES because it is highly threatened by illegal wildlife trade activities. To conserve pangolin and their habitats, it is necessary to understand the ecology of the animal. The study aims to determine the ecological information; activity time and habitat use of Sunda pangolin. Ecology of the Sunda pangolin was investigated by non-invasive method using camera traps in Sepilok Forest Reserve, Sabah. Other methods used were field observation and interviews. In this study, preferences of microhabitat were determined by analysing the termite nest distribution and den selection. Pangolin's activity time was also determined from camera trap data. As a result, a total of three visual evidences recorded in point location where there are high numbers of termites showing pangolin preferred habitat with high abundance of food source. The study also showed pangolin selected dens associated with larger trees, suggesting mature trees are very crucial for the survival of the species. General view on pangolin was collected through interviews with 101 respondents consisting of wildlife officers and local communities. The study also revealed that pangolin populations may decreased and expected to be threatened due to continual demand for pangolin scales. Challenges confronting Sunda pangolin and recommendation for future research of this species were also discussed.